Identifikasi Sifat-Sifat Fisik Mata Jaring Gillnet Terubuk (Tenualosa macrura) - Mardiah, Ratu Sari; Krisnafi, Yaser; Hutapea, Roma Yuli F; Mathius Tiku; Sony Anwar (Cenderawasih University, 2023)
The aim of this research is to identify changes in net geometry and analyze the correlation between the physical properties of the net and the geometry of the net that has been used for 1 to 3 years. The research used an experimental method by directly measuring the geometry of the net, namely mesh size, net diameter and knot height. The research also analyzed data on breaking strength and net elongation which were correlated with net geometry. The condition of the net when tested was dry. There were 4 treatments used in the research, namely control nets, nets that had been used by fishermen for 1, 2 and 3 years. The results of the research stated that the highest average gillnet mesh size value was for the 2 year net treatment and the lowest was 3 years. The highest average value of net diameter was the 1 year net and the lowest was the 2 year net. Meanwhile, the highest average gillnet node height is 1 year and the lowest is 3 years. The correlation value of net geometry with breaking strength has varying values. Breaking strength is closely related to the height of the knots in the mesh with a positive value of 0.77, whereas for mesh elongation all the mesh geometry indicators have negative values, so each increase in the mesh geometry value will decrease the elongation value.